Halal labelled cosmetics: what is it and what Korea can gain from it? - Wan Jusoh, Wan Jamaliah (2018)
Malaysia and Indonesia together accounted for nearly 60% of the Asia Pacific revenue in 2015, with skincare and makeup being the dominant products consumed. Personal care and beautycare launches in Malaysia outnumbered UK and Philippines, primarily due to local brands such as SimplySiti and IVY Beauty. The Korean craze which includes music and film has not eluded Malaysia. There has been a growing number of Malaysians who are addicted to the Korean Wave or “Hallyu”. This has been greatly due to the Korean soap operas, TV shows as well as pop stars and group performances. This has given the ideas to the young Malaysians that what originates from Korea is trendy and worth following. Several cosmetics and beauty care brands has penetrated the Malaysian market such as Laneige, Etude House, Tony Moly, Innisfree, Missha, Banila Co. and Talent cosmetic. With the exception of Talent cosmetic, all the brands are not halal certified. Talent cosmetics received the halal certification for 141 of its products from JAKIM in 2014. Therefore, the purpose of this paper is to provide empirical findings on the determinants of halal cosmetics and personal care usage in Malaysia. The findings from this paper will assist cosmetics and personal care companies to understand the consumer to market their products to the Muslims and non-Muslims who value halal certified products.